Audit Medik Skizofrenia - Soejono Prawirohardjo, Soejono Prawirohardjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1985)
The paper describes the Quality Assurance Program (QAP), including utilization review and patient care audit. A survey was carried out in Puri Nirmala.Hospital, a private mental hospital in Yogyakarta, during 3 months period between January - April 1984. The aim of the survey is, to evaluate schizophrenic in-patients based on 8 criteria: diagnostic procedures, reasons of admission, mental status after admission, length of stay, mortality, complications, therapy and laboratory examinations. 56 schizophrenic in-patients during the surveys period were evaluated. The result chows some deficiencies and shortcomings in the application of QAP. Finally, some recommendations are offered. Key Words: schizophrenia - quality assurance program - drug audit - nursing audit - complication audit.